LITERASI DIGITAL DALAM ETIKA KOMUNIKASI MEDIA SOSIAL DI ERA POST-TRUTH PADA GURU MA SEKABUPATEN GORONTALO UTARA - Ridwanto Djahuno; Idan I. Pakaya; Tiyara I. Lamato; Adriyanti Buheli; Saputri Ishak (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the level of digital literacy and communication ethics on social media among Madrasah Aliyah (MA) teachers in North Gorontalo Regency in the post-truth era. Using a qualitative approach, data was collected through in-depth interviews, observations, and analysis of related documents. The results show that although the term "digital literacy" is less familiar, teachers have understood the concept and importance of digital literacy in managing information. They demonstrate the ability to identify valid information and double-check it before disseminating it on social media. In addition, teachers' communication ethics are well considered, including accuracy and responsibility in sharing information. However, the study also found challenges related to the lack of formal training and supportive policies. Therefore, it is necessary to increase training programs and awareness of the importance of digital literacy and communication ethics to strengthen the role of teachers as role models in managing information in the digital era. The conclusion of this study emphasizes that with the right support, digital literacy and communication ethics can be an important foundation in facing information challenges in society